(untitled) (Progressive Agriculture, 2013)
The production and economics of GIFT strain of tilapia (Oreochromis niloticus) reared in nine seasonal small ponds at Bangladesh Agricultural University campus for a period of three months during August to October were evaluated. The experiment was arranged in three treatments (T) each with three replications. The ponds were drained, limed and fertilized with organic and inorganic fertilizers during preparation. After stocking the fishes the ponds were fertilized weekly with cowdung, urea and TSP. Supplementary feed was not given in T1, but rice bran and mustard oilcake were given in T2 and commercial pellet feed in T3. Some water quality parameters were monitored at regular intervals and they were within acceptable range for aquaculture. The survival rates were high (>95%) in all treatments. Significantly highest production (3941.50 kg/ha in three months) was found in T3 followed by T2 (1845.5 kg/ha) and T1 (972.50 kg/ha). Similarly, significantly highest net return (Tk. 61805.00/ha with benefit cost ratio of 1.45) was found in T3 followed by T2 (Tk.1339.00/ha with benefit cost ratio of 1.01) and T1 (Tk. 201.50/ha with benefit cost ratio of 1.00). DOI: http://dx.doi.org/10.3329/pa.v19i1.17360 Progress. Agric. 19(1): 97 - 104, 2008